Mourning the elegy: Robert Creeley's 'Mother's Photograph'. Issue 1 (2nd January 2017) - Steen, John
ABSTRACT: Although Robert Creeley is rarely considered an elegiac poet, he investigated problems of time and closure in elegiac writing earlier in his career than most critics have acknowledged, and by means unexplored by contemporary elegists like Allen Ginsburg and Sylvia Plath. Like Roland Barthes' La chambre claire (1980), Robert Creeley's 1986 poem 'Mother's Photograph' incorporates and interrogates an alternative technology of representation to resolve a crisis in the work of maternal mourning. The last in a series of elegies written over the course of 14 years, 'Mother's Photograph' suggests that Creeley, like Barthes, experienced the 'sporadic' temporality of grief and the surprising 'violence' attached to the photograph's elegiac use. While the series as a whole sheds light on the trajectory of Creeley's work and suggests a significant revision to existing accounts of elegy in mid-century literary history, the final poem speaks to issues of poetics engaged when a volatile genre, the elegy, is forced to account for the wordless revelations of an aesthetic object imbued with the aura of death. As it reflects on the series' gradual withdrawal from conventional elegy and its consolations, 'Mother's Photograph' turns toward the work of mourning elegy itself.